Workplace training & learning cases from cross-cultural perspectives - Gani, Aahad M. Osman (Prentice Hall, 2005)
This case book on workplace training & learning presents 18 case studies representing a variety of situations and approaches to training and learning in different work settings. Each case follows a similar format of presentation: organisational setting, business problem, training and development process, description of the training, results of the training, lessons learned, and questions for further study.